Mapping sign-tracking and goal-tracking onto human behaviors - Colaizzi, Janna M. (Neurosci Biobehav Rev, 2020)
As evidenced through classic Pavlovian learning mechanisms, environmental cues can become incentivized and influence behavior. These stimulus-outcome associations are relevant in everyday life but may be particularly important for the development of impulse control disorders including addiction. Rodent studies have elucidated specific learning profiles termed ‘sign-tracking’ and ‘goal-tracking’ which map onto individual differences in impulsivity and other behaviors associated with impulse control disorders’ etiology, course, and relapse. Whereas goal-trackers are biased toward the outcome, sign-trackers fixate on features that are associated with but not necessary for achieving an outcome; a pattern of behavior that often leads to escalation of reward-seeking that can be maladaptive. The vast majority of the sign- and goal-tracking research has been conducted using rodent models and very few have bridged this concept into the domain of human behavior. In this review, we discuss the attributes of sign- and goal-tracking profiles, how these are manifested neurobiologically, and how these distinct learning styles could be an important tool for clinical interventions in human addiction.